Infrastructure and Employment Creation in the Middle East and North Africa - Estache, Antonio; Ianchovichina, Elena; Bacon, Robert; Salamon, Ilhem (Washington, DC: World Bank, 2013)
The state of national labor markets has always been a concern for governments and development agencies such as the World Bank. Key labor market indicators, such as the rate of unemployment, send signals about the health of an economy and mirror citizens' attitudes. Being gainfully employed is an important aspect of an individual's well-being both financially and socially, as 'initial failures in finding a job can lead to persistent joblessness, a loss of interest in further schooling, delayed family formation, mental distress, and negative manifestations of citizenship' (World Bank 2007). Increased expenditure on infrastructure projects has a short-run effect on employment creation as more workers are hired to build infrastructure. These jobs last only during the investment phase of the project, and, without a continuous injection as in a stimulus-type program, such jobs will be temporary. However, the investment program will have created a larger stock of infrastructure capital and this permanent addition facilitates additional growth in the economy. The extra demand from this incremental growth creates more jobs, and these tend to be permanent. Furthermore, an employment experience in an infrastructure-related employment program, even if temporary, might improve the chance of being re-employed at a later date. This study capitalizes on the World Bank's long-standing knowledge on infrastructure, employment, and growth and applies it to the case of MENA to assess the employment creation potential of infrastructure investment.